ENCHANCING STUDENTS’ VOCABULARY MASTERY OF DESCRIPTIVE TEXT THROUGH WORD SEARCH GAME - Wakania, Gregoria Natalie; Sada, Clarry; Supardi, Iwan (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research is aimed at enhancing students’ vocabulary mastery of Descriptive Text at 8F class of SMPN 7 Sungai Raya in Academic Year 2017/2018. This research used Word Search Game as technique in teaching vocabulary. This research was done by giving students the test each cycle. The method of this research was a classroom action research, which consisted of 3 cycles. The teaching media of this research was pictures which are to train the students to enhance and memorize the words easily. The subject of this research was students of 8F class of SMPN 7 Sungai Raya in Academic Year 2017/2018. The research was conducted to solve the problem encountered by the students in vocabulary mastery. The technique of data collecting for this research was observation and test. The tools of data collecting were observation checklist, field note and measurement test. The result of this research showed that Word Search Game enhanced students’ vocabulary mastery in descriptive text. The students’ individual score in vocabulary also improved in teaching learning process. From this result, it can be concluded that students’ vocabulary mastery taught by Word Search Game had improved. In another word, this technique can help students in vocabulary mastery. Key Words: Enhancing, Vocabulary, Mastery, Word Search Game, Descriptive text.